A methodological guide for translating study instruments in cross‐cultural research: Adapting the 'connectedness to nature' scale into Chinese. Issue 11 (1st September 2020) - Cheung, Hubert; Mazerolle, Lorraine; Possingham, Hugh P.; Tam, Kim‐Pong; Biggs, Duan
Abstract: Ecologists and conservation scientists use social science research methods to carry out studies around the world. The language and cultural context in which study instruments are applied often differ from the context in which they were originally developed. Study instruments used in cross‐cultural research need to maintain equivalency in order to ensure that the results and conclusions are not affected. Translation is a crucial part of research design, so a carefully planned methodological approach needs to be taken to adapt existing tools. We present a clear, concise and easy‐to‐use procedure for researchers in conservation and ecology to translate study instruments. This five‐step guide first requires researchers to recruit a diverse and balanced team of translators, who are tasked with performing a series of forward and back‐translations. A committee approach is used to resolve differences in format, wording, grammar, sentence structure, item meanings, relevance and culturally specific references to reach a consensus on the best possible translation, which can then be pilot tested and validated. As a case study to demonstrate how our method works, we adapted the 'connectedness to nature' scale into Chinese. Originally created in English by Mayer and Frantz, the 'connectedness to nature' scale measures an individual's emotional connection to nature, which is an important predictor of environmental behaviour. It is theorized that reconnecting humans to the natural world can help mitigate environmental crises. Although no method is fail‐safe, by following the structured, five‐step method we present in this paper, ecologists and conservationists can employ a more thorough and rigorous approach to translating their study instruments for cross‐cultural research than commonly used methods like direct translation. Ultimately, researchers must decide on what translation procedures are appropriate for their work given constraints on time and resources.